问题 解答题
下面各题能简算的要简算.
4
5
-(
5
7
-
1
2
)=
1
4
-
3
7
+(
3
4
-
4
7
)=
11-
7
10
-
3
10
=
7
8
-
4
9
+
1
8
=
4
9
+
2
3
+
5
9
-
1
3
=
11
16
-(
5
16
+
3
8
)=
答案

(1)

4
5
-(
5
7
-
1
2
),

=

4
5
-
5
7
+
1
2

=

56
70
-
50
70
+
35
70

=

41
70

(2)

1
4
-
3
7
+(
3
4
-
4
7
),

=

1
4
-
3
7
+
3
4
-
4
7

=(

1
4
+
3
4
)-(
3
7
+
4
7
),

=1-1,

=0;

(3)11-

7
10
-
3
10

=11-(

7
10
+
3
10
),

=11-1,

=10;

(4)

7
8
-
4
9
+
1
8

=(

7
8
+
1
8
)-
4
9

=1-

4
9

=

5
9

(5)

4
9
+
2
3
+
5
9
-
1
3

=(

4
9
+
5
9
)+(
2
3
-
1
3
),

=1+

1
3

=1

1
3

(6)

11
16
-(
5
16
+
3
8
),

=

11
16
-
5
16
-
3
8

=

3
8
-
3
8

=0.

单项选择题
单项选择题